2002
DOI: 10.1143/jjap.41.5415
|View full text |Cite
|
Sign up to set email alerts
|

Low-Energy Penning Ionization Gauge Type Ion Source Assisted by RF Magnetron Discharge

Abstract: We study the competition between dispersion and absorption of doubly-dressed four-wave mixing (DDFWM) and dressed six-wave mixing. In the case of weak coupling fields limit, we find DDFWM signal is affected by destructive interference between four-wave mixing(FWM) and six-wave mixing as well as constructive interference between FWM and eight-wave mixing. By analysing the difference between two kinds of doubly dressing mechanisms (parallel cascade and nested cascade) in this opening five-level system, we can fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…On the other hand, broad-beam ion sources operating with gases at p ∼ 10 −4 Torr are designed for generating beams of singly charged positive ions for materials processing. They employ cold cathodes with end (or axial) ion extraction and are a combination of two discharges [34,35]. At such low pressures, the secondary discharge is used to provide additional ionization for the Penning discharge, resulting in a high-current, low-voltage operation mode.…”
Section: Penning Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, broad-beam ion sources operating with gases at p ∼ 10 −4 Torr are designed for generating beams of singly charged positive ions for materials processing. They employ cold cathodes with end (or axial) ion extraction and are a combination of two discharges [34,35]. At such low pressures, the secondary discharge is used to provide additional ionization for the Penning discharge, resulting in a high-current, low-voltage operation mode.…”
Section: Penning Cellsmentioning
confidence: 99%
“…Rf power can be coupled to a cold-cathode Penning discharge by direct connection of the opposing cathodes to an rf power supply, as illustrated in figure 6. Such a hybrid configuration has recently been employed for broad ion beam production by Abolmasov et al [35]. It was found that the use of rf powered electrodes as the cathodes for a dc Penning discharge can result in a low pressure (∼10 −4 Torr), high-current discharge mode.…”
Section: Rf and Microwave Couplingmentioning
confidence: 99%